Reviving Matrix for Nerve Reconstruction in Rabbit Model of Chronic Peripheral Nerve Injury With Massive Loss Defect - Rochkind, Shimon; Almog, Mara; Meilin, Sigal; Nevo, Zvi (Frontiers in Surgery, 2021)
Background and aims: The aim of this study was to investigate the innovative Guiding regenerative gel (GRG) and antigliotic guiding regenerative gel (AGRG) fillings for nerve conduits, prepared with FDA approved agents, and expected to provide an alternative to an autologous nerve graft and enabling reconnecting massive nerve gaps in rabbit model of chronic peripheral nerve injury with massive loss defect that simulates the human condition of chronic injury with large gap. Methods: The components and dosimetry for GRG and AGRG formulations were investigate on in-vitro nerve cell culture, in-vivo on 10mm reconstructed sciatic nerve of the 72 rats using different concentration of the agents and compeleted on rabbit model of the delyed (chronic) complete peripheral nerve injury with 25mm gap. The 40 rabbits underwent delayed (9 weeks after complete injury of the tibial portion of the sciatic nerve) nerve tube reconstruction of gap long 25mm. GRG and AGRG groups were compared with autologous and empty tube reconstructed groups. Rats and rabbits underwent electrophysiology and histochemical assessments (19 weeks for rats and 40 weeks for rabbits). Results: Application of AGRG significantly increases of about 78%, in neurite length per cell and showed to most promising effect on the neuronal outgrowth and total number of neurites increase of 4-folds. The electrophysiological follow up showed that AGRG treatment is the most promising for reconstruction of the tibial portion of the sciatic nerve with critical gap of 25 mm. The beneficial effect of AGRG was found when compared with the autologous nerve graft reconstruction. Thirty-one weeks post the second surgery (delayed reconstruction), histochemical observation showed significant regeneration after using AGRG neurogel, compared with the empty tube and succeeded to significant nerve regeneration nerve, as well as the autologous nerve graft and almost similar to healthy nerve. In conclusion, we demonstrate that in model of a delayed peripheral nerve repair with massive loss defect, the application of AGRG led to a stronger nerve recovery and can be alternative to autologous nerve graft.